Similarities and Differences between Clavicular Bacterial Osteomyelitis and Nonbacterial Osteitis: Comparisons of 327 Reported Cases - Nan Jiang; Ping Zhang; Wei-ran Hu; Zi-long Yao; Bin Yu (Journal of Immunology Research)
Background. Currently, both clavicular bacterial osteomyelitis (BO) and nonbacterial osteitis (NBO) remain not well understood owing to their much lower incidences. This study is aimed at summarizing similarities and differences between clavicular BO and NBO based on comparisons of literature-reported cases. Methods. We searched the PubMed and Embase databases to identify English published literature between January 1st, 1980, and December 31st, 2018. Inclusion criteria were studies evaluating clinical features, diagnosis, and treatment of clavicular BO and NBO, with eligible data for synthesis analysis. Results. Altogether, 129 studies with 327 patients were included. Compared with BO, clavicular NBO favored females (P<0.001) and age below 20 years (P<0.001) and mostly presented in a chronic phase (disease term exceeding 2 months) (P<0.001). Although local pain and swelling were the top two symptoms for both disorders, fever, erythema, and a sinus tract were more frequently found in BO patients (P<0.01). Although they both favored the medial side, lesions in the clavicular lateral side mostly occurred in BO patients (P=0.002). However, no significant differences were identified regarding the serological levels of white blood cell count (P=0.06), erythrocyte sedimentation rate (P=0.27), or C-reactive protein (P=0.33) between BO and NBO patients before therapy. Overall, the BO patients achieved a statistically higher cure rate than that of the NBO patients (P=0.018). Conclusions. Females, age below 20 years, and a long duration of clavicular pain and swelling may imply NBO. While the occurrence of a sinus tract and lesions in the lateral side may be clues of BO, inflammatory biomarkers revealed limited values for differential diagnosis. BO patients could achieve a better efficacy than the NBO patients based on current evidence.